Circadian rhythm and aryl hydrocarbon receptor crosstalk in bone marrow adipose tissue and implications in leukemia - Bihter Muratoğlu; Cansu Özdemir; Cemil Can Eylem; Tuba Reçber; Emirhan Nemutlu; İdil Yet; Duygu Uçkan-Çetinkaya (Scientific Reports)
Abstract Leukemic cells modulate the bone marrow microenvironment to enhance their survival. Lipolysis in bone marrow adipose tissue (BMAT) has emerged as a critical factor supporting leukemic cell survival, yet understanding its primary role in leukemia development remains limited. Fanconi anemia (FA), characterized by a predisposition to acute myeloid leukemia (AML) and hypersensitivity to environmental toxins, is a transitional model for studying leukemic transformation. İntegrated multi-omics analyses were conducted on BMAT-derived mesenchymal stem/stromal cells (MSCs) from healthy donors (HD), AML, and FA patients. These analyses revealed intricate interactions among genes, metabolites, and lipids. Particularly noteworthy were the effects observed following the inhibition of aryl hydrocarbon receptor (AhR) signaling by StemRegenin1 (SR1). BMAT-MSCs showed increased expression of epithelial-mesenchymal transition (EMT) genes in FA and AML, suggesting a potential shift towards cancer-associated fibroblasts in the dysregulated marrow microenvironment. Identification of potential circadian rhythm biomarkers (NPAS2, PER2, BHLHE40, PER3, CIART) in BMAT-MSCs indicates a link between related lipid metabolism genes (e.g., PTGS1, PIK3R1) and SR1 treatment, implicating them in lipolysis processes. Dysregulation of circadian rhythm-related genes (CIART, BHLHE40, NPAS2) in AML BMAT-MSCs, along with changes in circulating lipid metabolites like palmitate suggests their role in shaping the leukemia microenvironment. Upregulation of FABP5 and CD36 suggests a novel molecular mechanism involving FABP5 in AhR-mediated circadian regulation and identifies CD36 as a potential partner for FABP5 in BMAT-MSCs. Overall, this study unveils the interplay between AhR signaling, circadian rhythm, and the leukemia microenvironment in BMAT-MSCs, offering new insights into leukemia pathogenesis and therapeutic opportunities.